Arylethynyl Helices Supported by π‐Stacking and Halogen Bonding. Issue 5 (3rd May 2021) - Bowling, Nathan P.; Speetzen, Erin D.; Bosch, Eric
Abstract: Co‐crystallization of a pyridyl‐containing arylethynyl (AE) moiety with 1, 4‐diiodotetrafluorobenzene leads to unique, figure‐eight shaped helical motifs within the crystal lattice. A slight twist in the AE backbone allows each AE unit to simultaneously interact with haloarene units that are stacked on top of one another. Left‐handed (M) and right‐handed (P) helices are interspersed in a regular pattern throughout the crystal. The major driving forces for assembly are 1) halogen bonding between the pyridyl nitrogen atoms and the iodine substituents of the haloarene, with N⋅⋅⋅I distances between 2.81 and 2.84 Å, and 2) π‐π stacking of the haloarenes, with distances of approximately 3.57 Å between centroids. Halogen bonding and π‐π stacking not only work in concert, but also seem to mutually enhance one another. Calculations suggest that the presence of π‐π stacking modestly intensifies the halogen bonding interaction by <0.2 kcal/mol; likewise, halogen bonding to the haloarene enhances the π‐π stacking interaction by 0.59 kcal/mol. Abstract : Halogen bonding serves as a primary driving force for the formation of helices of pyridyl‐containing arylethynyl units with halorenes. The role of π‐π stacking in not only reinforcing the supramolecular construct, but also seemingly enhancing the strength of the halogen bond, is explored.